2019
DOI: 10.1093/jrr/rrz023
|View full text |Cite
|
Sign up to set email alerts
|

Dose–volume parameters and local tumor control in cervical cancer treated with central-shielding external-beam radiotherapy and CT-based image-guided brachytherapy

Abstract: Definitive radiotherapy for cervical cancer consists of external-beam radiotherapy (EBRT) and brachytherapy. In EBRT, a central shield (CS) reduces the dose to the rectum and bladder. The combination of whole-pelvic (WP)- and CS-EBRT and brachytherapy is the standard radiotherapy protocol in Japan. Despite clinical studies, including multi-institutional clinical trials, showing that the Japanese treatment protocol yields favorable treatment outcomes with low rates of late radiation toxicities, dose–volume para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 36 publications
2
27
0
5
Order By: Relevance
“…As a result, the five-year local control rate for stage III-IVA patients was as high as 90%, with no rectal toxicity greater than Grade 2 over a median follow-up of 60 months. Meanwhile, Okazaki et al reported the outcome of definitive chemoradiotherapy using CT-based IGBT for 103 patients with locally advanced cervical cancer [ 15 ]. That study aimed to achieve a HR-CTV (D90) of >6 Gy at each brachytherapy session, with a total EQD2 to the rectum (D2cc) of <75 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the five-year local control rate for stage III-IVA patients was as high as 90%, with no rectal toxicity greater than Grade 2 over a median follow-up of 60 months. Meanwhile, Okazaki et al reported the outcome of definitive chemoradiotherapy using CT-based IGBT for 103 patients with locally advanced cervical cancer [ 15 ]. That study aimed to achieve a HR-CTV (D90) of >6 Gy at each brachytherapy session, with a total EQD2 to the rectum (D2cc) of <75 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the total EQD2 3 to D 2cc for the fistulated part of the rectum was 57.7 Gy and that the fistulated part was not corresponding to the dose hotspot represented by the D 2cc of the whole rectum. This value of 57.7 Gy is unexpectedly low considering the data on dose‐volume constraints and the resultant rectal toxicity reported in previous studies (performed in the pre‐bevacizumab era), which employed the same radiotherapy strategy as used herein 3,13 . Ohno et al reported the outcome of definitive chemoradiotherapy for stage IB1–IVA cervical cancers (n = 80) 3 .…”
Section: Discussionmentioning
confidence: 94%
“…This value of 57.7 Gy is unexpectedly low considering the data on dose-volume constraints and the resultant rectal toxicity reported in previous studies (performed in the pre-bevacizumab era), which employed the same radiotherapy strategy as used herein. 3,13 Ohno et al reported the outcome of definitive chemoradiotherapy for stage IB1-IVA cervical cancers (n = 80). 3 In that study, the dose-volume constraint for the rectum was set at a total EQD2 3 to D 2cc of < 75 Gy, and no rectal toxicity greater than Grade 2 was observed after a median follow-up of 60 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the treatment planning of CT-based 3D-IGBT, dose prescription is performed based on the 3D-reconstructed volumes of the high-risk clinical target volume (CTV HR ) and those of the organs at risk (OARs), such as the sigmoid colon, the rectum, and the bladder [7,8]. CT-based 3D-IGBT achieves favorable tumor local control with minimal adverse effects on OARs [8,9].…”
Section: Introductionmentioning
confidence: 99%